La fortaleza de los pacientes con enfermedad crónica (2007)
The study was intended to determine the degree of correlation between levels of strength for health and state-trait anxiety in a sample of 200 patients created through non-probabilistic sampling. The following were the inclusion criteria: adults of both genders who have been diagnosed with a chronic illness and have a basic and occupationally-oriented education. The Roy Adaptation Model was used as the theoretical framework for the study. The design was descriptive, transverse and correlational. S. Pollock's strength questionnaire was used, along with Spielberger's self-assessment scale for state-trait anxiety. The instruments showed an acceptable internal consistency with a Cronbach alpha of .852 and.813 respectively. The data were collected from four health-care institutions in the towns of Tampico and Ciudad Madero, Tamaulipas, Mexico, and analyzed by means of a descriptive and inferential statistical study. SPSS, Version 13, was the statistical package used. The predominant age range was 45 to 64 years (54%); 55% of the sample is female, 48% has a primary education, and nearly 90% has a metabolic illness. The Spearman correlation coefficient between strength for health and state-trait anxiety was significant (-.570, value -p .000). Most of the participating population showed a moderate level of strength (83%) and anxiety (73%). According to the multiple regression analysis, the significant relationship between these two variables is not affected by age, gender or evolution of the chronic illness in terms of years. According to the data from the study, the greater the strength level among patients with chronic illnesses, the less the state-trait anxiety level. This suggests the need for further studies on these phenomena in the field of nursing, so as to provide theoretical-practical support for the design or improvement of care protocols focused on this aspect of human life.